Ketogenic diets composed of long-chain and medium-chain fatty acids induce cardiac fibrosis in mice - Felix Sternberg; Christina Sternberg; Andreas Dunkel; Taraneh Beikbaghban; András Gregor; Aleksander Szarzynski; Veronika Somoza; Ingrid Walter; Kalina Duszka; Barbara Kofler; Elena E. Pohl (Elsevier, 2023)
Purpose: Heart diseases are the leading cause of death worldwide. Metabolic interventions via ketogenic diets (KDs) have been used for decades to treat epilepsy, and more recently, also diabetes and obesity, as common comorbidities of heart diseases. However, recent reports linked KDs, based on long-chain triglycerides (LCTs), to cardiac fibrosis and a reduction of heart function in rodents. As intervention using medium-chain triglycerides (MCTs) was recently shown to be beneficial in murine cardiac reperfusion injury, the question arises as to what extent the fatty acid (FA)-composition in a KD alters molecular markers of FA-oxidation (FAO) and modulates cardiac fibrotic outcome. Methods: The effects of LCT-KD as well as an LCT/MCT mix (8:1 ketogenic ratio) on cardiac tissue integrity and the plasma metabolome were assessed in adult male C57/BL6NRJ mice after eight weeks on the respective diet. Results: Both KDs resulted in increased amount of collagen fibers and cardiac tissue was immunologically indistinguishable between groups. MCT supplementation resulted in i) profound changes in plasma metabolome, ii) reduced hydroxymethylglutaryl-CoA synthase upregulation, and mitofusin 2 downregulation, iii) abrogation of LCT-induced mitochondrial enlargement, and iv) enhanced FAO profile. Contrary to literature, mitochondrial biogenesis was unaffected by KDs. We propose that the observed tissue remodeling is caused by the accumulation of 4-hydroxy-2-nonenal protein adducts, despite an inconspicuous nuclear factor (erythroid-derived 2)-like 2 pathway. Conclusion: We conclude that regardless of the generally favorable effects of MCTs, they cannot inhibit 4-hydroxy-2-nonenal adduct formation and fibrotic tissue formation in this setting. Furthermore, we support the burgeoning concern about the effect of KDs on the cardiac safety profile.